Auditory Pathway Maturation in Full-term Small for Gestational Age Children: A Systematic Review with Meta-analysis - Dourivaldo Silva Santos; Luciene da Cruz Fernandes; Mara Renata Rissatto-Lago; Ana Caline Nóbrega Costa (International Archives of Otorhinolaryngology, 2023)
Introduction Factors of intrauterine growth restriction have been responsible for the births of full-term babies small for their gestational age (SGA). Scientific evidence points that this restriction can cause changes in the neural maturation process.